Strategy model in bus tracking and information application (BTA) towards smart mobility in urban spaces - Wong, Seng Yue; Koh, Keng Chye; Cheong, Wan Hoy; Hussain, Azman (Universiti Teknikal Malaysia Melaka, 2018)
Smart city can be defined as an urban space with complete and advanced infrastructure, intelligent networks and platforms, with millions of sensors among which people themselves and their mobile devices. Urban mobility is one of the global smart city project which offers traffic management in real-Time, management of passenger transport means, tracking applications and logistics, car sharing services, car park management and more smart mobility services. Due to the frustrating waiting time for the arrival of buses and the difficulty of accessing shuttle bus-related information in a one-stop centre, bus tracking and information application (BTA) is one the proposed solutions to solve the traffic problems in urban spaces. This paper is aimed to design and develop a bus tracking and information application in a selected city in Selangor state, Malaysia. Next, this application also provides an alternative to design public transport tracking and information application for the urban places in Malaysia. Furthermore, the application also provides a smart solution for the management of public infrastructures and urban facilities in Malaysia in future. Finally, the smart mobility model will be presented to uncover the extent on how BTA provide smart solutions in urban spaces which focus on informative, interactive, assistive and green mobility.